A reconnaissance study on tensile strength of bamboo based on global database. (2022) - Lee, G.Z.X.; Looi, D.T.W.; Choo, C.S.; Tsang, H-H.
Abstract: Bamboo is an alternative to conventional building materials such as concrete, steel, and timber. Compared to timber, in particular, bamboo reaches an age of maturity faster (typically three to four years to reach maturity). Hence, systematic farming of bamboos can provide a sustainable supply for the construction industry. In this study, three bamboo species native to Sarawak, Malaysia (namely Bambusa vulgaris, Dendrocalamus asper, and Gigantochloa levis ) were identified as potential materials for structural use in construction. Given that the tensile strengths of these local bamboos have not been characterized by extensive testing, a reconnaissance survey on the tensile strengths (obtained from coupon tests fabricated from bamboo culms) was carried out. Findings from the compiled database suggest that the reported average ultimate tensile strength of tested bamboo was less than half of the characteristic yield strength of steel, which unjustified the complete replacement of steel by bamboo in reinforced concrete. Also, the nodes (internal diaphragms and external ridge) have significantly lower strength than the internodes stem of the bamboo, contrary to previous researchers claiming that the periodic nodes have a beneficial biomechanical function.